Analisis Tingkat Kesehatan Koperasi Simpan Pinjam Pada Koperasi SMA Negeri 1 Peudada - Annisak, Maulina; ., Marliyah; Lubis , Arnida Wahyuni (CV. ITTC INDONESIA, 2023)
This research aims to determine the health level of savings and loan cooperatives at the SMA Negeri 1 Peudada cooperative. This research is descriptive research using qualitative methods with a case study approach. The subjects in this research were 2 people, namely the Treasurer and the Supervisory Board of the SMA Negeri 1 Peudada Cooperative. The object of this research is the financial report of the SMA Negeri 1 Peudada Cooperative since 2021 and the calculation of remaining business results as well as the problem credit report. The data analysis technique was carried out using an assessment approach which refers to the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 06/Per/Dep.6/IV/2016. The research results from the total score produced by assessing seven assessment aspects, namely capital, quality of productive assets, management, efficiency, liquidity, independence and growth as well as the identity of the cooperative show that the development of the Health Level of the Savings and Loans Cooperative at the SMA Negeri 1 Peudada Cooperative in 2021 with a final score obtained of 83.15 and included in the healthy category.